The Digital Age and Human Rights Protection in Indonesia: Legal Framework, Challenges, and Reform Directions - Setiyo Utomo (Faculty of Law, Universitas Sebelas Maret, 2025)
The digital age in Indonesia has changed social, economic, and legal domains, making human rights protection difficult. The rapid adoption of technology has exacerbated privacy and constitutional concerns due to data leaks, cybercrime, and speech restrictions. Digitalisation's impact on human rights protection and Indonesia's legal framework is examined in this study. The analysis uses conceptual, statutory, and doctrinal legal research. It highlights constitutional provisions, national legislation, the Information and Electronic Transactions and Personal Data Protection Law, and relevant comparative observations. Despite progress in sector-specific legislation, Indonesia's legal system remains fractured and unsuitable for comprehensive protection. Inadequate enforcement, legal uncertainty, public ignorance of digital rights, and digital divide increase vulnerabilities. The study emphasises that privacy, freedom of expression, and secure digital transactions are crucial to human rights in the digital age. It proposes unifying sectoral laws, improving law enforcement, and creating a data protection authority with explicit powers and resources. Multi-stakeholder governance, international collaboration, and digital literacy must be integrated into educational and public awareness programs. In Indonesia's digital revolution, these reforms must ensure that technological advancement supports human rights